Water‐Soluble (Pterin)rhenium(I) Complex: Synthesis, Structural Characterization, and Two Reversible Protonation–Deprotonation Behavior in Aqueous Solutions - Ragone, Fabricio (2012)
A new water-soluble complex, Re(CO)3(pterin)(H2O), was synthesized and characterized by 1H NMR and FTIR spectroscopy,and by a combination of three mass spectrometry techniques: MALDI, probe electrospray iniosation (PESI), and ESI. Because, unlike most metal-pterin complexes, the ReI complex is quite soluble in water, appropriate single crystals could be obtained for structural X-ray analysis. We report here the first solid state molecular structure containing a pterin ligand coordinated to the Re(CO)3 core. This determination revealed that strong H bonds between the hydrogen atom of the 2-amino group and crystallization water molecules give rise to a polymeric arrangement of Re(CO)3-(pterin)(H2O) complexes in the lattice. Protonation studies in aqueous solutions of the ReI complex showed two acid-base equilibriums with pKa1 = 3.9 and pKa2 = 8.8. pKa1 was assigned to the protonation equilibrium at N3 of the pterin ligand in the complex and pKa2 could be ascribed to the deprotonation of a coordinated water molecule.